Evaluation of novel Parkinson's disease candidate genes in the Chinese population - Chew, Elaine Guo Yan; Liany, Herty; Tan, Louis C.S.; Au, Wing-Lok; Prakash, Kumar-M.; Annuar, Azlina Ahmad; Chan, Anne Y.Y.; Lim, Shen Yang; Mok, Vincent; Chung, Sun Ju; Song, Kyuyoung; Liu, Jianjun; et al. (Elsevier, 2019)
Recent whole-exome sequencing studies in European patients with Parkinson's disease (PD) have identified potential risk variants across 33 novel PD candidate genes. We aim to determine if these reported candidate genes are similarly implicated in Asians by assessing common, rare, and novel nonsynonymous coding variants by sequencing all 33 genes in 198 Chinese samples and genotyping coding variants in an independent set of 9756 Chinese samples. We carried out further targeted sequencing of CD36 in an additional 576 Chinese and Korean samples. We found that only 8 of 43 reported risk variants were polymorphic in our Chinese samples. We identified several heterozygotes for rare loss-of-function mutations, including the reported CD36 p.Gln74Ter variant, in both cases and controls. We also observed 2 potential compound heterozygotes among PD cases for rare loss-of-function mutations in CD36 and SSPO. The other reported variants were common in East Asians and not associated with PD, completely absent, or only found in controls. Therefore, the 33 reported candidate genes and associated variants are unlikely to confer significant PD risk in the East Asian population.